Capital Market Response to COVID-19 Pandemic – A Systematic Review on Stock Volatility and Performance - Hamal, Janga Bahadur; Gautam, Rishi Raj (Marsyangdi Journal, 2021)
This paper aims to identify the impact of the COVID-19 pandemic on stock market volatility and market return as well as the impact of government response to the COVID-19 pandemic on stock market performance. To analyze the same, the paper has adopted Systematic Literature Review (SLR) approach and conducted a review of 40 journal articles published between between2020 to mid-2021. The paper identified that the short-term impact of the COVID-19 outbreak and government policy measures had a significant and adverse impact on stock market volatility, return and overall performance. In the longer term, the stock markets slowly started to stabilize and revive. This effect on the stock market was also attributed to investor sentiment and thus, in the later stages, targeted government response had a positive effect on boosting investor confidence towards the market.